The Impact of Job Analysis and Promotion Through Competency on Employee Performance at Raden Mattaher Regional General Hospital, Jambi Province - Irhamnida, Irhamnida; Zahari, M.; Sudirman, Sudirman (International Journal of Advanced Multidisciplinary, 2025)
The purpose of this study was to analyze the influence of job analysis and promotion on competency, analyze the influence of job analysis and promotion on performance, and analyze the influence of job analysis and promotion on performance through competency at Raden Mattaher Regional General Hospital, Jambi Province. The method used in this study was descriptive and quantitative statistics, using tabulation of respondent questionnaires as the basis for processing descriptive statistics and quantitative methods using the Structural Equation Model (SEM) and the Smart PLS 3.0 analysis tool. The research object in this study was job analysis and promotion through competency on employee performance at Raden Mattaher Regional General Hospital, Jambi Province, with a sample of 90 respondents from a total population of 881 employees. In accordance with the assessment of job analysis, promotion, competency, and employee performance at Raden Mattaher Regional General Hospital, Jambi Province, the job analysis had a total score of 4309, categorized as good. Furthermore, the promotion factor showed a total score of 3080, categorized as very good. Furthermore, the competency factor overview shows a total score of 2295, categorized as very high, while the employee performance factor overview shows a total score of 2580, categorized as high. In accordance with the analysis results using the Smart PLS 3.0 application, job analysis has a important impact on competency, promotion has a important impact on competency, Employee performance is positively and substantially impacted by job analysis, positively and substantially impacted by promotion, positively and substantially impacted by competency, as well as substantially impacted by job analysis through competency and promotion through competency.